The effect of exercises in the style of flexible resistance in developing the explosive and speed-distinguishing strength of the arms and legs and the strength and accuracy of shooting for handball players - Mohammed Headan, Hussam; Hkem Mohamed, Sardar (International Journal of Psychosocial Rehabilitation, 2020)
Handball is one of the games that witnessed a noticeable development in many vital joints, and this is represented in increasing the speed and strength of the game in both offensive and defensive moves. All of this needs an increase in the physical giving of the player during the match, and in order to be able to meet these difficult requirements It must be possessed by physical elements that qualify it to meet these requirements strongly and quickly at the same time, and the method of training with flexible resistances is one of the submethods of parallel training, which depends on the variation within the same training repetition, i.e. variation in the intensity of training in one exercise, which gives effective and focused results On the training goals that must be achieved as a result of training, through the use of elastic ropes and elastic sandal bands, it is one of the training means that gives a variable amount of intensity when used as well as the ease of dealing with them in exercise unlike other traditional resistances, and thus this helps to perform strength exercises with a path My movement is similar to performance and therefore the muscles working in actual performance will get effective training, which works to develop them positively, and this is what I proved The results that have been reached, the muscular ability represented by the explosive force and the strength marked by speed, have achieved a noticeable development and this has a positive impact on the correction power and its accuracy among the members of the research sample.